Optimization of the organization of nutrition for preschool children by increasing parental awareness about rational nutrition - Chernenko, O.; Vasyliev, Yu. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article considers the problem of forming parents' awareness of the rational nutrition of preschool children, which is a key factor in preserving and strengthening health, preventing diseases and ensuring the harmonious development of the child. The growing role of nutrition in preserving children's health, the insufficient level of awareness of parents, the influence of the family environment on the formation of a child's eating behavior, the increasing prevalence of overweight and deficient states in children, compliance with modern trends in educational work with parents, determine the relevance of the topic, emphasizing the combination of efforts of preschool educational institutions and the family in forming healthy eating habits in children by increasing the level of awareness of parents. The purpose of the study was to determine the level of awareness of parents of pupils of Sumy preschool educational institution No. 29 "Rosinka" and develop effective tools for its increase. The work used a set of methods: sociological (questionnaire), analytical (SWOT-analysis), statistical and mathematical modeling methods. The results of the study showed that the level of awareness of parents is 75.9%, while only 59.22% have a high level of knowledge, which indicates the need to strengthen educational work. SWOT analysis made it possible to identify the strengths and weaknesses of the institution's information activities, as well as identify opportunities for its improvement. The proposed optimization model of catering involves the use of such tools as online meetings, thematic weeks, workshops and the use of infographics, which has proven its effectiveness in combining accessibility and minimal costs. The article substantiates that the systematic application of these measures will contribute to increasing parental awareness, forming a responsible attitude towards children's nutrition and creating conditions for preserving their health. The results obtained can be used in the practical activities of teachers, medical workers and administrations of preschool institutions to improve the educational process and promote a healthy lifestyle.